Peranan Ulasan Secara Daring dan Rating terhadap Keputusan Pembelian Paket Wisata - Yulia Putri Herdinda; Andriansyah Bari; Astika Ulfah Izzati; Imas Permatasari; Alexandra Manoren; Davina Ramadhani Akbar (Jurnal Ilmu Manajemen, 2026)
This study aims to determine the influence of online customer reviews and ratings on the Google Review platform on purchasing decisions for tour packages at CV Help Group, Palembang. The research is motivated by the increasing reliance on digital platforms in shaping consumer purchasing behavior, particularly in the tourism industry. The research method used is a quantitative approach with multiple linear regression analysis techniques. Data were collected through questionnaires distributed to 87 respondents who had used CV Help Group’s services. The results show that both online customer reviews and ratings have a positive and significant effect on purchasing decisions, both partially and simultaneously. These findings confirm that online reviews and ratings are critical elements in shaping consumer perceptions and trust toward a product or service. Therefore, managing customer reviews and ratings strategically can serve as an effective marketing tool to enhance the company's competitiveness.